Cohesion in Lyrics of Songs with Covid-19 Prevention Theme as Public Education - Puspitawati, Yenny; Markhamah, M; Sabardila, Atiqa (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this research is to analyze cohesion markers contained in the song lyrics with theme of Covid-19 prevention. The type of research is descriptive qualitative. The data in this study are in the form of words, phrases, clauses, sentences and stanzas contained in the songs. Data were analyzed descriptively for both lexical and grammatical cohesion. The data sources include the lyrics of the song Di Rumah Saja by Sam Bimbo, Virus Corona by Rhoma Irama, Bangkit by Wan Rahil Apriliady, Cahaya dalam Kegelapan by Susilo Bambang Yudhoyono. The results showed that the most common cohesion marker found was lexical cohesion in the form of collocation. This indicates that there is an emphasis on the same meaning in every song lyric. The similarity of meaning is assembled and poured in every line and stanza which is full of meaningful messages for the community, so that the songs function as a medium for conveying messages to the community. The lyrics of the song provide educational value about: (1) appeal to people not to leave their homes so that the virus does not spread further, (2) humans asking God for protection to avoid covid-19, (3) invitation to rise up to fight covid-19, (4) when trials come, humans must be optimistic, pray to God, and share.